Study on laparoscopic spleen preserving distal pancreatectomy procedures comparing splenic vessel preservation and non-preservation - Nakamura, Yoshiharu (Transl Gastroenterol Hepatol, 2016)
BACKGROUND: The purpose of this study is to investigate whether two types of laparoscopic spleen-preserving distal pancreatectomy (Lap-SPDP) techniques are being implemented safely. The study compares the clinical outcomes from laparoscopic Warshaw operation (Lap-W) with those from laparoscopic splenic vessels preserving SPDP (Lap-SPDP-VP) and considers the role of those operations. METHODS: On August 2013, the Warshaw technique was introduced to our institution and 17 patients with a lesion in the distal pancreas who underwent Lap-SPDP by December 2015 were enrolled. Six patients who underwent a Lap-W and 11 patients who underwent a Lap-SPDP-VP were investigated retrospectively. RESULTS: In the Lap-W and Lap-SPDP-VP patients, the sizes of the tumors were 46.5±31.2 and 25.7±14.9 mm [Probability (P) value =0.0913)]; the operative times were 287 min (range, 225–369 min) and 280 min (range, 200–496 min); the blood loss was 95 mL (range, 50–200 mL) and 60 mL (range, 0–650 mL); the length of the postoperative hospital stay was 12 days (range, 8–43 days) and 11 days (range, 7–28 days); median follow-up was 19 months (range, 13–28 months) and 23 months (range, 6–28 months), respectively. There was no case of symptomatic spleen infarction in either group. However, partial infarctions of the spleen without symptoms were observed by computed tomography in three out of six cases (50%) in the Lap-W. No patient required reoperation and the postoperative mortality was zero in both groups. All patients were alive and recurrence-free at the end of the follow-up period. Collateral veins around the spleen developed in 83.3% (five out of six patients) in the Lap-W and developed in 12.5% (one out of eight patients) in the Lap-SPDP-VP. A significant difference was observed between groups (P=0.0256). Gastric varices developed in 33.3% (two out of six patients) in the Lap-W. However, no case of rupture of varices, or other late phase complications was observed in either group. CONCLUSIONS: Both the Lap-W and Lap-SPDP-VP were found to be safe and effective, and in cases in which the detachment work of the splenic vessels from the tumor or the pancreatic parenchyma is difficult, performing Lap-W, rather than Lap-SPDP-VP, is considered appropriate. While Lap-SPDP is recommended for patients with benign or low grade malignant diseases, long-term follow-up to monitor hemodynamic changes in splenogastric circulation is considered needed.